ENHANCING ENGLISH WRITING SKILLS THROUGH ARTIFICIAL INTELIGENCE TECHNOLOGIES AND SELF-REGULATED STRATEGIES IN DIFFERENTIATED INSTRUCTION FOR MULTILEVEL CLASSROOMS (International Conference on Modern Science and Scientific Studies, 2025)
This article explores the integration of Artificial Intelligence (AI) technologies and self-regulated learning (SRL) strategies to support differentiated writing instruction in multilevel classrooms. Grounded in Tomlinson’s (2001) differentiation model, the paper examines how AI tools can address differences in cognitive styles, learning preferences, and readiness levels, while fostering student autonomy. Research highlights the effectiveness of adaptive AI platforms in providing personalized feedback, scaffolding writing tasks, and promoting metacognitive skills. By synthesizing findings from Anderson (2007), Santangelo & Tomlinson (2009), and Chachoui & Elmediouni (2019), this study underscores the necessity of differentiated writing instruction and the role of AI in enhancing SRL. The discussion concludes with practical recommendations for educators in Uzbekistan’s multilingual classrooms.